Model Analisis Keperluan Bahasa Arab Untuk Pelancongan Islam Di Selangor: Kajian Awal - Mohammad Imran Ahmad; Ghazali Zainuddin; Siti Rosilawati Ramlan; Mohammad Najib Jaffar (Global Academic Excellence, 2024)
Non-Indexed Publication